Language teacher multilingualism in Norway and Russia: Identity and beliefs. (29th August 2020) - Calafato, Raees
Abstract: Multilingualism has witnessed growing interest as a subject of academic study and as a state to aspire to for many of the world's citizenry. In tandem with this growing interest, countries around the world have started to implement foreign language curricula at schools that seek to prepare the coming generations to thrive in an increasingly multilingual global environment. In this respect, language teachers are likely to play a pivotal role in promoting the learning of multiple languages among students, with their beliefs about multilingualism informing their practices. This study reports on the beliefs of 460 secondary school teachers of English, French, German, Spanish, Italian, and Chinese in Norway and Russia regarding the benefits of being or becoming multilingual, the affordances of multilingual teachers, and the promotion of multilingualism in their respective countries. The findings indicated statistically significant differences between the participants based on the number of languages they taught and, to some extent, their country of residence. The observed differences hold important implications for teacher education programs and initiatives promoting the use of multilingualism as a resource in language education.